ANALISIS STRATEGI HUBUNGAN MEDIA PT KERETA API INDONESIA DAOP 1 JAKARTA SAAT MUDIK LEBARAN 2018 - Fajar Widianto; Sardi Duryatmo; Mariana Rista Ananda Siregar (Jurnal Penelitian Sosial Ilmu Komunikasi, 2020)
The background of this research is the growth of mass media in Indonesia. Meanwhile, one of the public relations activities is responding to the interests of the media to provide information to the public. This study was conducted to analyze the media relations strategy run by PT Kereta Api Indonesia (Persero) Jakarta, in the context of Eid Mubarak Holiday 2018. The research used a qualitative method, with data sources derived from primary data and secondary data. The author uses expert triangulation to test the validity of the data obtained. This study indicated that establishing a relationship with the media is very important. Public relations and the media are two parties who need each other. Public relations requires publication from the media, while the media need information to be published as news. Keyword: eid Mubarak; Indonesia railways company; media relations; public relation